Enrichment and Association of Bacteria and Particulates in Salt Marsh Surface Water - Harvey, R. W. (1980)
Elevated counts of bacteria were found during outgoing tides in surface microlayers (∼300 μm) of Sippewissett salt marsh, Falmouth, Massachusetts, and Palo Alto salt marsh, Palo Alto, California. At both sampling sites, the degrees by which bacteria were concentrated into the surface microlayer were linearly dependent upon surface concentration of particulate material. A significant percentage of bacteria in the microlayer were found to be attached to particulate material, while bacterial populations in the subsurface water were largely planktonic. Proportions of the bacterial populations which could be grown on seawater nutrient agar were also greater in the microlayer than in the subsurface waters and were positively correlated with the fraction of bacteria attached to particulate matter. Data from these studies suggest that particulates in the microlayer waters of the salt marsh influenced the observed increase in both the readily grown and the total numbers of bacteria.